1977
DOI: 10.1148/125.1.141
|View full text |Cite
|
Sign up to set email alerts
|

The Nonspecificity of Absorption Coefficients in the Differentiation of Solid Tumors and Cystic Lesions

Abstract: Eleven lesions of the brain were analyzed and compared; they had absorption coefficients uniformly at the cerebrospinal fluid (CSF) level following contrast enhancement, and ranged from benign to malignant and solid to cystic. Grossly solid tumors may have absorption coefficients on the CT scan equal to CSF even after contrast enhancement. Absorption coefficients are misleading as histological indicators and in diagnosis; it is impossible to separate cystic from non-cystic, benign from malignant, and neoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In two cases, two specimens were necessary, three patients had three specimens, and two patients had four specimens taken before a histological diagnosis could be made. 4 Volume ofsample The volume of sample, from which a definitive histological diagnosis was obtained, was evaluable in 71 biopsies. In 48 biopsies (67%) the volume of sample was less than 2 mm3.…”
Section: General Aspectsmentioning
confidence: 99%
“…In two cases, two specimens were necessary, three patients had three specimens, and two patients had four specimens taken before a histological diagnosis could be made. 4 Volume ofsample The volume of sample, from which a definitive histological diagnosis was obtained, was evaluable in 71 biopsies. In 48 biopsies (67%) the volume of sample was less than 2 mm3.…”
Section: General Aspectsmentioning
confidence: 99%
“…PULLAN et al (1978) worked on the characterisation of regions in a CT image using statistical central moments (such as mean, standard deviation and skewness) obtained from histograms of CT values and a gradient measure (taken as a simplified measure of texture) within delimited regions, with application to brain tumours and lesions of the spleen and liver. KRAMER et al (1977) reported on work similar to that of PULLAN et al LATCHAW et al (1977) opined that CT is non-specific in the separation of solid tumours and cystic lesions in the brain.…”
Section: Tissue Characterisation Using Ctmentioning
confidence: 81%
“…Some authors have reported success in using CT units to differentiate between tissues that are visually similar in CT images (KRAMER et al, 1977;PULLAN et al, 1978;MATEGRANO et al, 1977;WILLIAMS et al, 1980), whereas others have reported failure in the same task (LATCHAW et al, 1977;FOGLIA et al, 1989). Although the measurement of the linear attenuation coefficient of tissues in vitro can be performed with good precision (RAo and GREGG, 1975;PHELPS et al, 1975), several sources of error can degrade the performance of (1977).…”
Section: Tissue Characterisation Using Ctmentioning
confidence: 99%
“…Acute hemorrhage has previously been shown to be highly echogenic and sharply circumscribed corresponding histologically to the dimensions of the clot (31,33,34,69). Hypodense areas appear within glioblastomas and are often seen by CT following treatment (24,65,77,105). However, the mean density of such a hypodense area does not distinguish cyst from central necrosis or solid tumor (65).…”
Section: Characterization Of Secondary Brain Tumor Characteristics (Nmentioning
confidence: 99%
“…Hypodense areas appear within glioblastomas and are often seen by CT following treatment (24,65,77,105). However, the mean density of such a hypodense area does not distinguish cyst from central necrosis or solid tumor (65). Intraoperative HRUS imaging has been very useful at distinguishing cystic from solid parts of brain tumors (27,37,38,42,89).…”
Section: Characterization Of Secondary Brain Tumor Characteristics (Nmentioning
confidence: 99%